All that is solid melts into air : the experience of modernity - Berman, Marshall (New York [etc.] : Penguin books, 1988)
The political and social revolutions of the nineteenth century, the pivotal writings of Goethe, Marx, Dostoevsky, and others, and the creation of new environments to replace the old—all have thrust us into a modern world of contradictions and ambiguities. In this fascinating book, Marshall Berman examines the clash of classes, histories, and cultures, and ponders our prospects for coming to terms with the relationship between a liberating social and philosophical idealism and a complex, bureaucratic materialism.

From a reinterpretation of Karl Marx to an incisive consideration of the impact of Robert Moses on modern urban living, Berman charts the progress of the twentieth-century experience. He concludes that adaptation to continual flux is possible and that therein lies our hope for achieving a truly modern society.
Keywords: teorija književnosti; književna kritika/modernizam; civilizacija -- 19. stoljeće; civilizacija -- 20. stoljeće